Percepções de estudantes do ensino médio politécnico sobre atividades de pesquisa realizadas na disciplina de seminário integrado no âmbito das ciências da natureza - Souza, Mayara Medaglia Leães de (2015)
The research reported on this dissertation focused on a significant pedagogical chance started on 2011-2012 period, in Rio Grande do Sul state scenario: the State Secretary of Education Proposal to Polytechnic High School implementation. In this scenario, the research, as a pedagogical principle, occupy, from a theoretical point of view, privileged space. However, it is necessary to evaluate how students are located in this reality and how the Integrated Seminar discipline addresses the research. Therefore, on the research, were sought answers to the following question: How Polytechnic High School students realize the research developed under public schools in Porto Alegre on the Integrated Seminar discipline from Natural Sciences area? The assumptions underpinning this research are grounded on the conceptions of polytechnic, the principles of curriculum restructuring in Rio Grande do Sul and in the investigation as a pedagogical principle in High School. The data were collected through recorded interviews with focus groups of students from eight schools of Porto Alegre macrozones, whose answers were analyzed through Discursive Textual Analysis – ATD, in order to perceive the understanding of students in relation to the Polytechnic High School,specially the research experiences.Can be stated as main conclusions that the texts that support the proposal of the Polytechnic High School are consistent from a theoretical point of view and the research as a pedagogical principle has highlight by its importance on the students development of citizenship and autonomy. However, it is observed, through the testimony of students, that in the eight schools investigated, the assumptions of polytechnic and didactic-methodological actions to achieve its objectives have not been fully appropriated by the teachers yet. Also, in the view of the students interviewed, is quite poor the pedagogical support of official agencies to teachers regarding the implementation of the proposal. In relation to the researches conducted in the studied schools in the scope of Integration Seminar discipline, based on the vision of the students, it appears that the actions are quite distant than those related by the authors that deal with research as pedagogical and methodological principle.